2022
DOI: 10.1097/qai.0000000000003014
|View full text |Cite
|
Sign up to set email alerts
|

Randomized Controlled Trial of Healthy Divas: A Gender-Affirming, Peer-Delivered Intervention to Improve HIV Care Engagement Among Transgender Women Living With HIV

Abstract: Background:Transgender women are disproportionately affected by HIV and are less likely to be optimally engaged in care than other groups because of psychosocial challenges. With community collaboration, we developed Healthy Divas, an individual-level intervention to increase healthcare empowerment and gender affirmation to improve engagement in HIV care. Healthy Divas comprises 6 peer-led individual sessions and one group workshop facilitated by a healthcare provider with expertise in HIV care and transgender… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 55 publications
0
6
0
Order By: Relevance
“…Mechanisms that rely on community advisors can be particularly valuable, [29][30][31] as are approaches that find trusted community partners for their ground operations. The strategy of activating community members as "peers" to foster engagement in self-care has provided some initial success in lesbian, gay, bisexual, transgender, queer (LGBTQ) groups 32 and could translate into outreach for research purposes.…”
Section: Diverse Communities Have To Be Effectively Engaged In Resear...mentioning
confidence: 99%
“…Mechanisms that rely on community advisors can be particularly valuable, [29][30][31] as are approaches that find trusted community partners for their ground operations. The strategy of activating community members as "peers" to foster engagement in self-care has provided some initial success in lesbian, gay, bisexual, transgender, queer (LGBTQ) groups 32 and could translate into outreach for research purposes.…”
Section: Diverse Communities Have To Be Effectively Engaged In Resear...mentioning
confidence: 99%
“…For example, while a large majority of studies on COVID-19 addressed the general population, HIV studies frequently focused on interventions targeting specific groups identified as vulnerable [e.g. 37 , 40 ]. They were also more likely to consider outreach approaches to CICICE in the contexts in which people live and work [ 36 ].…”
Section: Resultsmentioning
confidence: 99%
“…The few studies that considered the role of community-based surveillance (which often depends on the work of CHWs at the local level) noted increases in case reporting by comparison with passive surveillance systems (e.g. [ 37 , 50 ]). However, these studies were mostly small-scale observational or pilot studies [ 33 ].…”
Section: Resultsmentioning
confidence: 99%
“…Gender-affirmative PrEP systems necessitate for trans people to receive the necessary PrEP care continuum services [36] while also highly valuing and ensuring that trans people's gender identity and treatment goals are medically, socially, and structurally recognized and supported-to maximize the benefits of PrEP within trans communities directly [15,37]. In the context of HIV care, this includes the critical and comprehensive integration of HIV care with gender-affirming health services, which has been shown to improve engagement and retention for achieving viral suppression [38][39][40]. There have been some efforts to implement and evaluate genderaffirmative PrEP programs in existing healthcare settings [29,41]; however, additional efforts are warranted to address PrEP barriers across the personal/biological, social, structural socio-ecological levels.…”
Section: Persistence For Gender-affirmative Prep Systems and Trans En...mentioning
confidence: 99%